The Experience of East Texan School Librarians Who Participate in Self-Censorship - Casas, Jessica (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2025)
This literature review aims to synthesize research on the self-censorship practices of school librarians in Texas while also examining and interpreting the self-censorship experience. Various peer reviewed articles published within the last 20 years were analyzed for information on self-censorship practices and experiences. While self-censorship is opposed by all librarians, the studied school librarians have admitted to participating in self-censorship for a variety of reasons such as fear of reprimand, personal biases, and recent legislation changes. This literature review will also include recommendations for school librarians on avoiding self-censorship.